Sodium citrate contributes to the platelet storage lesion. Issue 6 (22nd February 2019) - Getz, Todd M.; Turgeon, Annette; Wagner, Stephen J.
Abstract : BACKGROUND: Sodium citrate has become the preferred anticoagulant used for apheresis collection and has been included in commercial platelet additive solutions (PASs) since PAS‐II. It was suggested that citrate be included in PASs to prevent spontaneous aggregation. Reports in cell lines and cord blood have demonstrated that concentrations of citrate present in PAS formulations (10 mM) cause apoptosis. We evaluated whether the removal of citrate from PAS‐III could improve platelet storage. STUDY DESIGN AND METHODS: Study 1 evaluated the effects of a citrate dose response on the storage of platelets in 65% PAS containing sodium chloride, sodium acetate, and phosphate. Study 2 compared the cell quality and function of platelets stored in 65% citrate‐free PAS‐III or PAS‐III containing 10 mM of citrate. Measurements included cell count, blood gases, flow cytometry analysis of surface activation markers, and aggregation. RESULTS: Study 1 identified that inclusion of citrate in PAS resulted in a dose‐dependent increase in glucose utilization, lactate formation, P‐selectin expression, phosphatidylserine (PS) exposure, and reactive oxygen species (ROS) formation. Study 2 showed similar results in which platelets stored in citrate‐free PAS‐III benefited through better maintenance of glucose utilization with less lactate production, P‐selectin expression, PS exposure, and ROS formation compared to citrate‐containing PAS‐III. Platelets stored in citrate‐free PAS‐III had aggregation responses that were at least 10% greater than those platelets stored in PAS‐III. CONCLUSION: Storage of apheresis platelets in citrate‐free PAS‐III improved multiple storage parameters including glucose utilization, lactate production, P‐selection expression, PS exposure, and ROS formation and resulted in a modest increase in aggregation.